Investigation on the Formation of Laser Transverse Pattern Possessing Optical Lattices - Wang, Xin; Zhang, Zilong; Gao, Yuan; Zhao, Suyi; Jie, Yuchen; Zhao, Changming (Frontiers in Physics, 2022)
Optical lattices (OL) with diverse transverse patterns and optical vortex lattices (OVL) with special phase singularities have played vital roles in the fields of atomic cooling, particle manipulation, quantum entanglement and optical communication. As a matter of consensus till now, the OL patterns are generated by coherently superimposing multiple transverse modes with a fixed phase difference through the transverse mode locking (TML) effect. There are phase singularities in the dark area of this kind of OL pattern, so it is also called OVL pattern. However, in our research, it is found that some high-order complex symmetric OL patterns can hardly be analyzed by TML model. Instead, the analysis method of incoherent superposition of mode intensity could be applied. The OL pattern obtained by this method can be regarded as in non-TML state. Therefore, in this paper we mainly study the distinct characteristics and properties of OL patterns in TML and non-TML states. Through intensity comparison, interferometry and beat frequency spectrum, we can effectively distinguish OL pattern in TML and non-TML states, which is of great significance to explore the formation of laser transverse pattern possessing OL.